2019
DOI: 10.1136/heartjnl-2019-315103
|View full text |Cite
|
Sign up to set email alerts
|

In vivo alpha-V beta-3 integrin expression in human aortic atherosclerosis

Abstract: ObjectivesIntraplaque angiogenesis and inflammation are key promoters of atherosclerosis and are mediated by the alpha-V beta-3 (αvβ3) integrin pathway. We investigated the applicability of the αvβ3-integrin receptor-selective positron emission tomography (PET) radiotracer 18F-fluciclatide in assessing human aortic atherosclerosis.MethodsVascular 18F-fluciclatide binding was evaluated using ex vivo analysis of carotid endarterectomy samples with autoradiography and immunohistochemistry, and in vivo kinetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Moreover, Qiao et al 35 reported a novel osteopontin-targeted nanoprobe, which was applied in both MRI and FLI of macrophages in atherosclerosis in vivo . Jenkins et al 36 used the PET radiotracer 18F-fluciclatide to target the α v β 3 -integrin receptor, which was upregulated in angiogenesis and inflammation under atherosclerosis conditions in vivo . Due to their low positive predictive values, these imaging tracers require further evidence to confirm their role in discriminating vulnerable from stable plaques 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Qiao et al 35 reported a novel osteopontin-targeted nanoprobe, which was applied in both MRI and FLI of macrophages in atherosclerosis in vivo . Jenkins et al 36 used the PET radiotracer 18F-fluciclatide to target the α v β 3 -integrin receptor, which was upregulated in angiogenesis and inflammation under atherosclerosis conditions in vivo . Due to their low positive predictive values, these imaging tracers require further evidence to confirm their role in discriminating vulnerable from stable plaques 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrin αvβ3 is expressed by activated endothelial cells, as well as macrophages. In a study of 46 patients with atherosclerosis who underwent PET imaging with the αvβ3 tracer 18 F-fluciclatide, uptake of this tracer in the aorta was higher in patients with myocardial infarction than stable angina and was correlated with measures of aortic atherosclerotic burden [57]. Other αvβ3-targeted tracers that have been evaluated for use in atherosclerosis include 18 F-Galacto-RGD and 18 F-Flotegatide [58][59][60].…”
Section: Tracers For Imaging Adjunctive Atherosclerotic Processesmentioning
confidence: 99%
“…The data from 46 patients presented by Jenkins et al represent the largest prospective cohort of patients with atherosclerosis imaged using an α v β 3 tracer 1. In a related study, the group previously reported that 18 F-fluciclatide could accurately identify areas of acute myocardial infarction (MI), and predict the likelihood of functional recovery in impaired, but viable, myocardium 3.…”
Section: αVβ3 Integrin Pet Imaging In Atherosclerosismentioning
confidence: 99%
“…However, several key pathogenic processes known to increase the likelihood of an acute plaque event can be tracked in vivo using positron emission tomography (PET). In their Heart paper, Jenkins et al 1 examine the utility of 18 F-fluciclatide, an α v β 3 integrin-binding PET tracer, for imaging atherosclerosis. This intriguing study adds great momentum in the push to identify novel methods for imaging molecular signatures of high-risk plaques, and raises several important broader considerations for the field.…”
mentioning
confidence: 99%